Legal analysis of the regulation of Alternative Dispute Resolution (ADR) in international contract law: A case study in Russia and Indonesia - Aprinisa, Aprinisa; Santoso, Niki Agus; Fita, Gia Ayu (Priviet Social Sciences Journal, 2026)
The increasing volume of cross-border trade and investment has positioned international contracts as the primary legal instrument governing global business relationships. Along with this development, the potential for contractual disputes between parties subject to different legal systems has intensified. Litigation before national courts is often considered ineffective in resolving international contract disputes because of jurisdictional constraints, lengthy procedures, and difficulties in the recognition and enforcement of judgments. Consequently, Alternative Dispute Resolution (ADR) has emerged as a more flexible and efficient mechanism within international contract law. This study aims to analyze the legal regulation of ADR in international contract law through a case study of Russia and Indonesia. This study employs normative legal research methods using statutory, conceptual, and comparative approaches. The data are derived from primary, secondary, and tertiary legal materials relevant to the regulation of ADR in both countries. The findings indicate that both Russia and Indonesia have normatively adopted international ADR principles, particularly arbitration, and are parties to the 1958 New York Convention. Nevertheless, significant differences exist in the implementation and effectiveness of ADR, influenced by the characteristics of their respective legal systems, policies, and judicial practices. This study concludes that although the normative frameworks governing ADR in Russia and Indonesia are largely aligned with international standards, further strengthening of consistent application and legal certainty is required to ensure the optimal functioning of ADR in the resolution of international contract disputes.